Thermal Study of Anhydrides Cured Tetrafunctional Cardo Epoxy Resin. (5th September 2013) - Patel, Jignesh P.; Parsania, Parsotam H.
Abstract : Tetrafunctional cardo epoxy resin (EBCF) was cured by using 10 wt% maleic anhydride (MA), pyromellitic dianhydride (PMDA), phthalic anhydride (PA), tetrahydrophthalic anhydride (THPA), tetrabromophthalic anhydride (TBPA), and tetrachlorophthalic anhydride (TCPA) as hardeners at 120°C for 40–105 min (gel time) and then postcured 1 h at 130°C. Gel time is found to depend on the structure of the anhydrides used. Cured samples were found insoluble in common solvents. Cured and uncured EBCF were characterized by FTIR, DSC, and TGA techniques. Cured and uncured resins followed multistep degradation reactions. Kinetic parameters, namely, order of degradation, energy of activation, frequency factor, and entropy change, were determined according to the Anderson-Freeman method and interpreted in light of the nature of hardeners used for curing purpose. The resins followed integral or fractional order degradation kinetics. Complex degradation reactions are due to different types of linkages in cured resins. Both nature and structure of resin and hardeners affected the curing behavior and the resultant thermal properties of the cured resins.